O dyskursie Olszowskiego „De archiepiscopatu gnesnensi”: - - Ryś, Anna (Prace Polonistyczne, 2019)
The article presents the arguments used by Primate Andrzej Olszowski in the De archiepiscopatu Gnesnensi to justify the hierarchical superiority of the Gniezno metropolis towards bishops in the Polish-Lithuanian Commonwealth. The reason for the text’s publication was a dispute between the Primate Olszowski and Andrzej Trzebicki, bishop of Cracow, who refused to give Olszowski the right to crown King Jan III Sobieski in the Wawel Cathedral. Trzebicki held that Cathedral was outside the dioceses of Gniezno. The conflict was settled by the Pope in favor of the Primate Olszowski. The published text collects materials from the Church and Archbishopric history, which justified the privilege of the priority of the Gniezno metropolis in the Commonwealth.